2016
DOI: 10.18805/ijar.v0i0f.3801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding water washed neem (Azadirachta indica) seed cake and salt sprinkled neem (Azadirachta indica) leaves on growth performanceand nutrient digestibility in Osmanabadi kids

Abstract: Twenty four Osmanabadi weaned male kids with average live weight of 10.80 kg were divided into four equal groups and fed with WWNSC and salt sprinkled neem leaves for 182 days to study the effect on growth performance and nutrient digestibility. The daily gain in body weight was significantly (Pis less than 0.05) higher in kids fed with salt sprinkled neem leaves individually than kids fed with WWNSC individually and in combination with salt sprinkled neem leaves. The DM, DCP and TDN intake in terms of per cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…Wanapat et al (2000); Muralidharan et al (2015) demonstrated that cellulose digestion is limited when ruminal pH reaches values below 6.0. Ruminal VFA concentrations and fermentation rates are correlated (Leng and Leonard, 1965;McDonald et al, 1995;Korake et al 2016) and this relationship was also demonstrated in the present study (ruminal VFAs and digestibility). These results are in contrast to Koster et al (1996) reported that TVFA increased dramatically in response to supplemental rumen degradable protein fed to beef cows.…”
Section: Resultssupporting
confidence: 86%
“…Wanapat et al (2000); Muralidharan et al (2015) demonstrated that cellulose digestion is limited when ruminal pH reaches values below 6.0. Ruminal VFA concentrations and fermentation rates are correlated (Leng and Leonard, 1965;McDonald et al, 1995;Korake et al 2016) and this relationship was also demonstrated in the present study (ruminal VFAs and digestibility). These results are in contrast to Koster et al (1996) reported that TVFA increased dramatically in response to supplemental rumen degradable protein fed to beef cows.…”
Section: Resultssupporting
confidence: 86%
“…The intake of milk replacer and starter supplement was recorded daily. On day 65, hip and wither heights and thoracic girth were measured (Korake et al, 2016). The clinical cases pneumonia, diarrhea, or otitis were recorded, diagnosed and treated with aminoglycoside or beta-lactam antibiotics.…”
Section: Growth Performance and Disease Incidencementioning
confidence: 99%
“…A variety of nutritional strategies can be used in calves during the first few months of life to ensure higher growth performance and better health and to reduce the incidence of infectious diseases (Devant and Marti, 2020). The use of feed supplements, such as phytobiotics, has been associated with improved immunity of early weaned calves and higher daily weight gain associated with digestibility efficiency (Korake et al, 2016). Similarly, in experiments with calve leukocytes treated with phytobiotic the results showed an increase in bactericidal activity and reduction of cases of diarrhea in newborn calves (Teixeira et al, 2015).…”
Section: Introductionmentioning
confidence: 96%